OP0037 Evaluation of skin involvement in systemic sclerosis patients by using two ultrasound transducers with different frequency. (15th June 2017) - Ruaro, B; Sulli, A; Paolino, S; Pizzorni, C; Ghio, M; Alessandri, E; Trombetta, AC; Cosso, C; Cutolo, M
Abstract : Background: The modified Rodnan skin score (mRSS) is the validated method to evaluate the extension of skin involvement in systemic sclerosis (SSc) and to distinguish between patients with limited cutaneous skin involvement (lcSSc, skin involvement is confined to the extremities) or diffuse (dcSSc) (1, 2). Recently several studies have demonstrated that skin high frequency ultrasound (US) is a valid and reproducible technique to measure dermal thickness (DT) in patients with SSc (3–6). Objectives: To compare the values of DT obtained by two ultrasound transducers with different frequency (18 MHz and 22 MHz) in evaluating the DT in lcSSc patients and healthy controls. Methods: Thirty-seven lcSSc patients (mean age 62±13SD years, mean disease duration 5±5SD years) and 37 healthy controls (CNT) sex and age matched were enrolled after informed consent. Both US transducers of 18 and 22 MHz (Esaote, Genova) were used to evaluate DT in the seventeen areas of the skin (zygoma, fingers, dorsum of hands, forearms, arms, chest, abdomen, thighs, legs, feet) of SSc patients where Rodnan skin score (mRSS) is usually assessed. Skin US was also performed in the same seventeen areas of CNT, looking for DT differences in comparison with lcSSc patients. Statistical analysis was carried out by non parametric tests. Results: DT evaluated with the 22 MHz probe was found significantly higher in all body areas in comparison with the 18 MHz transducer, both in lcSSc patients (p<0.01) and in CNT (p=0.05). The median difference of DT values between the two probes was of 0.11 millimetres in lcSSc patients (minimum 0.0023, maximum 0.28 mm) and 0.01 millimetres in CNT (minimum 0.0029, maximum 0.03 mm). Of interest, in lcSSc DT evaluated by 18 MHz transducer was recognized significantly higher (p<0.001) also in four out of six skin areas where the mRSS was found normal (score=0) (upper-arms, chest and abdomen), with exclusion of thighs (p=0.08), in contrast with the classification of lcSSc. However, by using the 22 MHz transducer a statistically significantly higher median DT was showed in all skin areas, included thighs (p<0.01). Finally, a positive statistically significant correlation was observed between the two transducers in the evaluation of DT (p<0.0001), as well as between both probes and mRSS (p<0.0001 for both). Conclusions: This study suggests that subclinical dermal involvement may be detectable by skin high frequency US already in patients with limited cutaneous SSc. This study confirms that DT can be better assessed in SSc patients by using a 22 MHz US probe, and suggests that DT might be underestimated by using US probes of lower frequency (18 MHz). However, the DT values obtained using both probes resulted significantly correlated together and with the mRSS. References: Clements PJ, et al. Arthritis Rheum 2000;43:2445–54. Moore TL, et al. Rheumatology 2003;42:1559–63. Sulli A, et al. Ann Rheum Dis. 2014;73:247–51. Czirják L, et al. Ann Rheum Dis. 2007;66:966–9. Hesselstrand R, et al. Rheumatology 2008;47:84–7. Kaloudi O, et al. AnnRheum Dis.2010;69:1140–3. Disclosure of Interest: None declared